2012
DOI: 10.1017/s0967199412000196
|View full text |Cite
|
Sign up to set email alerts
|

Crucial surviving aspects for vitrified in vitro-produced bovine embryos

Abstract: The objective of the present study was to correlate some parameters (cleavage, blastocyst production, quality degree score, total cell number, fresh apoptosis and lipid content) with embryo survival after cryopreservation. A total of 1727 in vitro-produced bovine blastocysts were used to establish the parameters (mean ± standard error of the mean (SEM)) for cleavage (85.6 ± 0.8), blastocyst production (39.9 ± 1.4), quality degree score (1.6 ± 0.1), total cell number (140.1 ± 2.9), fresh apoptosis (20.8 ± 1.1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 41 publications
(91 reference statements)
0
12
0
1
Order By: Relevance
“…Improvements to cryosurvival after vitrification were observed with the use of inhibitors of fatty acid synthesis [ 19 , 21 , 63 ], lipolytic agents [ 64 , 65 ], antioxidants [ 66 ] or molecules capable of modulating the molecular mechanisms of lipid uptake [ 67 , 68 ]. A possible explanation for our absence of positive results on cryopreservation in relation to embryos produced with lower lipid content, may be related with other factors that influence their quality and consequently, affecting embryo sensitivity to vitrification [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improvements to cryosurvival after vitrification were observed with the use of inhibitors of fatty acid synthesis [ 19 , 21 , 63 ], lipolytic agents [ 64 , 65 ], antioxidants [ 66 ] or molecules capable of modulating the molecular mechanisms of lipid uptake [ 67 , 68 ]. A possible explanation for our absence of positive results on cryopreservation in relation to embryos produced with lower lipid content, may be related with other factors that influence their quality and consequently, affecting embryo sensitivity to vitrification [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…As reported in adipocytes, the elevation of cAMP levels by forskolin, stimulates lipolysis and reduces the amount of lipids in porcine oocytes and embryos [ 14 , 15 ] and bovine oocytes [ 16 ]. In these studies, reduced lipids led to an improvement in cryotolerance.…”
Section: Introductionmentioning
confidence: 98%
“…This impairment occurs due to the physical and chemical damages induced during the cryopreservation process (Overstrom, 1996;Baguisi et al, 2000). Sudano et al (2012a) reported the effects of this damage by comparing the apoptosis rate caused by the stress of cryopreservation between fresh and vitrified blastocysts. In this study, there was a 2.4-fold increase (P < 0.0001) in the apoptosis rate of vitrified (49.4 ± 1.9) in relation to fresh embryos (20.8 ± 1.1).…”
Section: Cryopreservation Of Bovine Embryosmentioning
confidence: 99%
“…Studies have shown that the fetal calf serum (FCS) concentration affects the number of cytoplasmic lipid droplets of embryos (Leroy et al, 2005;Sudano et al, 2012a). Moreover, in vitro embryos cultured in a serum-free medium had decreased lipids and higher cryotolerance (Pereira and Marques, 2008).…”
Section: Strategies To Increase the Cryotolerance Of In Vitro Embryosmentioning
confidence: 99%
“…In vitro production (IVP) of bovine embryos was performed as previously described [22,31], unless otherwise noted. Only oocytes with three or more compact layers of cumulus cells and homogeneous cytoplasm were used.…”
Section: Embryo Productionmentioning
confidence: 99%